Communication, Religion and Politics in the Western World of the Digital Age - Frunză, Sandu (Journal for the study of religions and ideologies, 2025)
Today we are witnessing a revival of the spirit of religious fundamentalism in the political discourse of the European Union countries. A discourse of violence unfolds in the form of a new alliance between religion and politics is present among some Western political leaders. These forms of political communication are facilitated, on the one hand, by the political discourse of the populist parties, and on the other hand, using communication technologies to transmit political messages. They occur despite the fact that one of the gains of the postmodern world was the secularization of public life, the rule of law and political communication. In order to understand what is happening to political constructions in the era of the development of artificial intelligence, we have resorted to the perspective on communication formulated by Aurel Codoban, one of the most important Romanian philosophers. An unavoidable theme is that of otherness and identity construction. Artificial intelligence cannot be constituted as an otherness in relation to which the human being can build his own identity or the identity of the community to which he belongs. However, in the digital age, communication constructs reality, and in this process, communication technologies and especially artificial intelligence can be instrumentalized in the construction of discourse that can lead to the construction of identity in general and political identity in particular. Everything takes place in the context of a dialectic of the sacred and the profane in which the development of communication technologies enhances the collaboration between the human being and artificial intelligence.